Validity and reliability of the Brazilian portuguese version of the Australian national university – Alzheimer’s disease risk index (ANU-ADRI) - Borges, Marcus Kiiti; Jacinto, Alessandro Ferrari [UNESP]; Citero, Vanessa Albuquerque (FapUNIFESP (SciELO), 2018)
The ANU-ADRI is a self-report tool that assesses risk for Alzheimer’s Disease (AD). Objective: To validate an adapted Portuguese version of this instrument and to carry out the reliability Test-Retest of the ANU-ADRI in Brazil. Methods: In this longitudinal study, the sample was formed (n=100) by two groups (A and B): each comprising 50 patients assisted by GPs (general practitioners) or specialists in dementia. All participants were cognitively healthy upon screening using the MMSE. The ANU-ADRI was applied at baseline (Test) and again within 1 week of the test (Retest). Results: There was a correlation between the mean scores of the ANU-ADRI Test and Retest (r=0.918, P<0.001). Group A had higher ANU-ADRI scores than those of group B (P<0.05). There was a moderate negative linear relation between the ANU-ADRI and MMSE scores (r= –0.353, P<0.001). Conclusion: The ANU-ADRI is a valid and reliable instrument to assess whether community-dwelling Brazilians are at greater risk for AD. Low levels of education were associated with higher risk scores on the ANU-ADRI.
Validade e confiabilidade da versão brasileira do índice de risco da doença de alzheimer da “australian national university” (ANU-ADRI)
Keywords: Alzheimer’s disease; Dementia; Geriatric assessment; Primary prevention; Risk factors